Label‐free Electrochemical Aptasensor for Carcino‐embryonic Antigen Based on Ternary Nanocomposite of Gold Nanoparticles, Hemin and Graphene. Issue 5 (15th December 2015) - Liu, Zhiguang; Wang, Yuxuan; Guo, Yujing; Dong, Chuan
Abstract: In this report, a label‐free electrochemical aptasensor for carcino‐embryonic antigen (CEA) was successfully developed based on a ternary nanocomposite of gold nanoparticles, hemin and graphene nanosheets (AuNPs‐HGNs). This nanocomposite was prepared by decorating gold nanoparticles on the surface of hemin functionalized graphene nanosheets via a simple wet‐chemical strategy. The aptamer can be assembled on the surface of AuNPs‐HGNs/GCE (glassy carbon electrode) through Au‐S covalent bond to form the sensing interface. Hemin absorbed on the graphene nanosheets not only acts as a protective agent of graphene sheets, but also as an in situ probe base on its excellent redox properties. Gold nanoparticles provide with both numerous binding sites for loading CEA binding aptamer (CBA) and good conductivity to promote the electron transfer. The current changes, which are caused by CEA specifically binding on the modified electrode, are exploited for the label‐free detection of CEA in a very rapid and convenient protocol. Therefore, the method has advantages of high sensitivity, wide linear range (0.0001–10 ng mL −1 ), low detection limit (40 fg mL −1 ) and attractive specificity. The results illustrate that the proposed label‐free electrochemical aptasensor has a potential application in the biological or clinical target analysis for its simple operation and low cost. Abstract :